2010
DOI: 10.1111/j.1745-7599.2010.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and autonomy: Perceptions among nurse practitioners

Abstract: Collaboration between NPs and physician colleagues is said to improve the quality and cost of health outcomes and also leads to professional satisfaction. Further research into the relationships between collaboration and autonomy are necessary to understand these complex concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
69
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 20 publications
(40 reference statements)
10
69
1
1
Order By: Relevance
“…The nurses in this study had lower professional autonomy than the nurse practitioners in the USA, but this difference is expected with regard to the duties and potential authority of nurse practitioners in the USA. 27,29,32,36 This means that the nurses in the present study do not perceive that they have enough power nor receive an adequate amount of support and probably they feel barriers in obtaining their rights or they have a lower legal authority. 18,28 The existing differences in the autonomy score of nurses in this study with studies elsewhere could be explained by the barriers of the nurses' professional autonomy such as hospital rules and traditional mode of supervision and control, 18 hierarchical relations between physicians and nurses, and high workload in Iran's health-care systems.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The nurses in this study had lower professional autonomy than the nurse practitioners in the USA, but this difference is expected with regard to the duties and potential authority of nurse practitioners in the USA. 27,29,32,36 This means that the nurses in the present study do not perceive that they have enough power nor receive an adequate amount of support and probably they feel barriers in obtaining their rights or they have a lower legal authority. 18,28 The existing differences in the autonomy score of nurses in this study with studies elsewhere could be explained by the barriers of the nurses' professional autonomy such as hospital rules and traditional mode of supervision and control, 18 hierarchical relations between physicians and nurses, and high workload in Iran's health-care systems.…”
Section: Discussionmentioning
confidence: 75%
“…27 In another studies, it was 117.3 ± 12.5 29 and 123 ± 12.7. 27,29,32 Findings about readiness subscale showed that the participating nurses had medium levels of skill, mastery and competence in performing their duties. The nurses in this study had lower professional autonomy than the nurse practitioners in the USA, but this difference is expected with regard to the duties and potential authority of nurse practitioners in the USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Greece, there is still lack of advanced nursing clinical roles, resulting in diminished autonomy and probably low professional status (27) . Indeed, it has been shown that advanced clinical nurses tend to regard the quality of collaboration with physicians as being high (28) . There were a number of limitations in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to NP practice include limitations on prescriptive authority, reduced reimbursement rates, organizational restraints, public perceptions, and lack of support from other healthcare providers (Maylone, Ranieri, Griffin, McNulty, & Fitzpatrick, 2011;Poghosyan, Nannini, & Clarke, 2013). In its 2010 report entitled The Future of Nursing, the Institute of Medicine (2010) recommended relaxing state laws regulating NP practice (Kuo, Loresto, Rounds, & Goodwin, 2013;Poghosyan et al, 2012) to accommodate the millions of patients who will gain access to primary care as a result of healthcare reform.…”
Section: Current Relevance Of the Np Rolementioning
confidence: 99%